COLLABORATIVE LANGUAGE PEDAGOGY AND STUDENTS’ ACADEMIC ACHIEVEMENT IN ENGLISH LANGUAGE IN EKITI STATE - Babalola, Joseph (Advances in Social Sciences Research Journal, 2019)
Abstract This study examined the effect of collaborative teaching on students’ academic achievement in English language in Ekiti State. The population consisted of 161 Junior Secondary school three students made up of 103 males and 58 females selected from Federal Science and Technical College, Usi-Ekiti, Ekiti State. A total of 20 students (10 males) and (10 females) randomly selected from the school constituted the sample. The twenty students were divided into two groups-Experimental and Control. Group A was used as experimental group while group B was used as the control group. Two research questions and two hypotheses guided the study. The data collected were analysed using mean and percentages to answer the research questions while t-test and chi-square statistics were used to test the hypotheses. The major findings show that the students taught with Collaborative Teaching Strategy (CTS) achieved significantly better outputs than those of the control group. The study also discovered that there was no significant gender difference in the students’ achievement in English language. Based on the findings of this study, it was recommended that collaborative teaching strategy should be adopted as a more effective approach to teaching of English Language at the Junior Secondary School levels.